Fatal renal failure as the first manifestation of sarcoidosis diagnosed on necropsy in a young man: a case report. Issue 10 (27th September 2004) - Awasthi, A; Nada, R; Malhotra, P; Goel, R; Joshi, K
Abstract : Renal involvement as the first manifestation of sarcoidosis is rare and has never been reported in India. This report describes a 35 year old man who was admitted to the emergency department with a clinical diagnosis of acute on chronic renal failure, secondary to obstructive uropathy. Postmortem examination unexpectedly revealed disseminated sarcoidosis.